Kemasan, Kualitas Produk, dan Harga Berpengaruh terhadap Keputusan Pembelian Keripik Ikan Tawar Mina Sari di Wonogiri - Veronica Veronica; Khabib Alia Akhmad; Nur Hadi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The aim of this research is to determine the influence of packaging, product quality and price on purchasing decisions for Mina Sari freshwater fish chips in Wonogiri. The type of research used was quantitative research, where the population taken was 50 buyers of Mina Sari freshwater fish chips, with a research sample of 25 people. The sampling method is probability sampling and data collection is using a questionnaire. Data analysis by means of research instrument tests includes validity tests, reliability tests, classic assumption tests including normality tests, multicollinearity tests, and heteroscedasticity tests, hypothesis tests include T tests, F tests, and R tests. The resulting research is the significant influence of packaging on decisions Purchase of Mina Sari Wonogiri freshwater fish chips. The significant influence of product quality on purchasing decisions for Mina Sari Wonogiri freshwater fish chips. The significant influence of price on the decision to purchase Mina Sari Wonogiri freshwater fish chips. Packaging, product quality and price simultaneously influence the decision to purchase Mina Sari freshwater fish chips in Wonogiri.